Towards a Process Algebra for Shared Processors - Buchholtz, Mikael; Andersen, Jacob; Løvengreen, Hans Henrik (Electronic notes in theoretical computer science, 2002)
We present initial work on a timed process algebra that models sharing of processor resources allowing preemption at arbitrary points in time. This enables us to model both the functional and the timely behaviour of concurrent processes executed on a single processor. We give a refinement relation that describes that one process is more deterministic than another. Applications of the model for process scheduling, programming language semantics, and kernel development are outlined.